2006
DOI: 10.1242/jeb.02531
|View full text |Cite
|
Sign up to set email alerts
|

Improving sneaky-sex in a low oxygen environment: reproductive and physiological responses of male mosquito fish to chronic hypoxia

Abstract: SUMMARY Few studies have examined the adaptive significance of reversible acclimation responses. The aerobic performance and mating behaviour of the sexually coercive male eastern mosquito fish (Gambusia holbrooki)offers an excellent model system for testing the benefits of reversible acclimation responses to mating success. We exposed male mosquito fish to normoxic or hypoxic conditions for 4 weeks and tested their maximum sustained swimming performance and their ability to obtain coercive mati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…1). This supports the prediction for fewer behavioural displays in males acclimated to low DO relative to those acclimated to high DO, a pattern that is consistent with many short‐term studies that have demonstrated negative effects of hypoxia on male behavioural displays including aggressive encounters and mating displays (Sneddon & Yerbury, 2004; Abrahams et al , 2005; Marks et al , 2005; Carter & Wilson, 2006). More generally, this finding supports several reports in the literature of reduced activity levels in fishes exposed to hypoxia (Hubbs et al , 1967; Schurmann & Steffensen, 1994; Chapman & McKenzie, 2009).…”
Section: Summary Of Repeated Measures Ancova To Detect the Effects Ofsupporting
confidence: 88%
“…1). This supports the prediction for fewer behavioural displays in males acclimated to low DO relative to those acclimated to high DO, a pattern that is consistent with many short‐term studies that have demonstrated negative effects of hypoxia on male behavioural displays including aggressive encounters and mating displays (Sneddon & Yerbury, 2004; Abrahams et al , 2005; Marks et al , 2005; Carter & Wilson, 2006). More generally, this finding supports several reports in the literature of reduced activity levels in fishes exposed to hypoxia (Hubbs et al , 1967; Schurmann & Steffensen, 1994; Chapman & McKenzie, 2009).…”
Section: Summary Of Repeated Measures Ancova To Detect the Effects Ofsupporting
confidence: 88%
“…The most likely explanation for this difference lies within the coercive reproductive strategy of G. holbrooki . Female mosquitofish almost never copulate willingly, and successful copulations are usually forced ( Bisazza et al, 2001 ; Carter and Wilson, 2006 ). Termed ‘sneaky sex’, males stealthily approach females and rapidly insert their gonopodium to release sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown hypoxia to influence reproductive viability of fish by disrupting the hormonal regulation of sexual maturation and spawning (Wu et al, 2003;Dabrowski et al, 2003;Carter and Wilson, 2006;Thomas et al, 2006;Shang et al, 2006;Landry et al, 2007;Wang et al, 2008;Wu, 2009). Gene expression analyses show widespread changes in expression of genes related to erythropoiesis, angiogenesis, glycolysis (favoring anaerobic respiration), oxidative phosphorylation and steroid hormone metabolism (or steroidogenesis) (Gracey et al, 2001;Ton et al, 2003;Shang et al, 2006;Marques et al, 2008;Martinovic et al, 2009).…”
Section: Introductionmentioning
confidence: 99%